Deep genomic analysis of malignant peripheral nerve sheath tumor cell lines challenges current malignant peripheral nerve sheath tumor diagnosis - Magallón-Lorenz, Míriam; Terribas, Ernest; Ortega-Bertran, Sara; Creus-Bachiller, Edgar; Fernández, Marco; Requena, Gerard; Rosas, Inma; Mazuelas, Helena; Uriarte-Arrazola, Itziar; Negro, Alex; Lausová, Tereza; Castellanos, Elisabeth; et al. (iScience, 2023)
Malignant peripheral nerve sheath tumors (MPNSTs) are soft-tissue sarcomas of the peripheral nervous system that develop either sporadically or in the context of neurofibromatosis type 1 (NF1). MPNST diagnosis can be challenging and treatment outcomes are poor. We present here a resource consisting of the genomic characterization of 9 widely used human MPNST cell lines for their use in translational research. NF1-related cell lines recapitulated primary MPNST copy number profiles, exhibited NF1, CDKN2A, and SUZ12/EED tumor suppressor gene (TSG) inactivation, and presented no gain-of-function mutations. In contrast, sporadic cell lines collectively displayed different TSG inactivation patterns and presented kinase-activating mutations, fusion genes, altered mutational frequencies and COSMIC signatures, and different methylome-based classifications. Cell lines re-classified as melanomas and other sarcomas exhibited a different drug-treatment response. Deep genomic analysis, methylome-based classification, and cell-identity marker expression, challenged the identity of common MPNST cell lines, opening an opportunity to revise MPNST differential diagnosis.
Online verfügbar 31. Januar 2023, Artikelversion 9. Februar 2023
Gesehen am 10.07.2023